Genetic variation in N-use efficiency and associated traits in Indian wheat cultivars - Nehe⁠, A.S.; Misra, S.; Murchie, E.H.; Chinnathambi, K.; Foulkes⁠, M.J. (Elsevier, 2018)
Nitrogen (N) fertilizer represents a significant cost for the grower and may also have environmental impacts through nitrate leaching and N⁠2O (a greenhouse gas) emissions associated with denitrification. The objectives of this study were to quantify the genetic variability in N-use efficiency (NUE) in Indian spring wheat cultivars and identify traits for improved NUE for application in breeding. Twenty eight bread wheat cultivars and two durum wheat cultivars were tested in field experiments in two years in Maharashtra, India. Detailed growth analysis was conducted at anthesis and harvest including dry matter (DM) and N partitioning. Senescence of the flag leaf was assessed from a visual score every 3–4 days from anthesis to complete flag-leaf senescence and fitted against thermal time to estimate the onset and end of post-anthesis senescence. Grain yield (GY) was reduced under low N (LN) by an average of 1.59t ha⁠−1 (−28%). Significant N×genotype level interaction was observed for grain yield and NUE. Above-ground N uptake at harvest was reduced from 162kg N ha⁠−1 under high N (HN) to 85kg N ha −1 under low N (LN) conditions, while N-utilization efficiency (grain DM yield per unit crop N uptake at harvest; NUtE) increased from 32.7 to 44.6kg DM kg −1 N. Genetic variation in GY under LN related mainly to variation in N uptake at harvest rather than NUtE; and the N×genotype effect for GY was mainly explained by the interaction for N uptake at harvest. Averaging across years, the linear regression of onset of flag-leaf senescence on GY amongst cultivars was significant under both HN (R2 0.16. p<0.05) and LN (R2 0.21, p<0.05) conditions. Onset of flag-leaf senescence was positively associated with N uptake at anthesis under HN (R2 0.34, p<0.001) and LN (R2 0.22, p<0.01) conditions. Flag-leaf senescence timing was not associated with post-anthesis N uptake. It is concluded that increased N accumulation at anthesis was correlated with flag-leaf senescence timing and that N accumulation at anthesis is an important trait for enhancing grain yield and NUE of wheat grown under low to moderate N supply in India.